PENGEMBANGAN MATERI AJAR TEKS BERITA BERBANTUAN APLIKASI GENIALLY PADA SMP KELAS VII SMPN 6 PERCUT SEI TUAN - Roh Ulitona, Anastasia; Naelofaria, Salmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The objectives of this research and development are (1) to determine the process of developing news text teaching materials assisted by the Genially application for class VII students of SMPN 6 Percut Sei Tuan, (2) to determine the form of news text teaching materials assisted by the Genially application for class VII students of SMPN 6 Percut Sei Tuan, and (3) to determine the level of feasibility of the resulting product in the form of news text teaching materials assisted by the Genially application for class VII students of SMPN 6 Percut Sei Tuan. The development model used in this teaching material development is the Borg and Gall model, but only up to the design revision stage. The data collection methods used in this study were observation, interviews, and questionnaires. The results of this research and development are: (1) the process of developing news text teaching materials assisted by the Genially application consists of 5 stages, namely (a) the potential and problem analysis stage, (b) data collection, (c) product design, (d) design validation, and (e) design revision; (2) the form of news text teaching materials assisted by the Genially application is in the form of interactive learning media designed to resemble a digital application based on self-navigation and can be accessed by users via an online link; (3) the feasibility of developing news text teaching materials assisted by the Genially application obtained an average value of 4.6 (very feasible) from the material validator and 4.4 (very feasible) from the media validator. The results of this study indicate that news text teaching materials assisted by the Genially application in grade VII of SMPN 6 Percut Sei Tuan are valid and suitable for use in learning news texts.